Legacy Pengadilan Hibrida di Kamboja: Memajukan Peradilan yang Bebas dan Tidak Memihak? - Somaly Kum (Jurnal HAM, 2024)
The mandate of the Extraordinary Chambers in the Courts of Cambodia (ECCC) concluded in 2022, marking the end of its nearly two-decade presence in Cambodia. Established as a hybrid court through a collaboration between the Cambodian government and the United Nations, the ECCC operated under a unique framework combining foreign and domestic laws, personnel, and judges. While the caseload of the court ended in early 2022, there are remaining legacies for Cambodians. This research investigates the legacy of the ECCC concerning fair trial rights and examines how national staff apply their experiences from the ECCC in the national courts. The article relies on document analysis and in-depth interviews with seven former and current Cambodian domestic court staff who worked at the ECCC to analyze three elements of fair trial rights: the right to adequate time and facilities to prepare a defense, the right to legal representation and to be present at trial, and the right to presumption of innocence. This paper argues that the legacy of the ECCC lies in its contribution to build the national staff's capacity on fair trial rights in domestic courts in Cambodia. However, significant challenges remain, as the fair trial rights envisioned and put in place in the ECCC cannot be currently delivered by Cambodian domestic judicial system.